Section 8.1 Introduction to the Laplace Transforms

Problem 6.

Prove that if
[tex]f(t)↔ F(s)[/tex]
then
[tex] {t}^{k} f(t)↔ {( - 1)}^{k} {F}^{k} (s).[/tex]
Hint: Assume that it's permissable to the differentiate the integral
[tex]F(s)={∫}^{ \infty } _{0} {e}^{ - st} f(t)dt[/tex]
with respect to s under the integral sign.

Section 81 Introduction to the Laplace Transforms Problem 6Prove that if texft Fstexthen tex tk ft 1k Fk stexHint Assume that its permissable to the differentia class=

Respuesta :

Let k = 1, for a start. By definition of the Laplace transform,

[tex]\displaystyle F(s) = \int_0^\infty f(t) e^{-st} \, dt[/tex]

Differentiate both sides with respect to s :

[tex]\displaystyle F'(s) = \frac{d}{ds} \int_0^\infty f(t) e^{-st} \, dt[/tex]

[tex]\displaystyle F'(s) = \int_0^\infty \frac{\partial}{\partial s}  \left[f(t) e^{-st}\right] \, dt[/tex]

[tex]\displaystyle F'(s) = \int_0^\infty -t f(t) e^{-st} \, dt[/tex]

so that [tex]t f(t) \leftrightarrow (-1)^1 F^{(1)}(s) = -F'(s)[/tex] is indeed true.

Suppose the claim is true for arbitrary integer k = n, which is to say that [tex]t^n f(t) \leftrightarrow (-1)^n F^{(n)}(s)[/tex]. Then if k = n + 1, we have

[tex]F^{(n+1)}(s) = \dfrac{d}{ds} F^{(n)}(s)[/tex]

Consider the two cases:

• If k = n + 1 is even, then n is odd, so

[tex](-1)^n F^{(n)}(s) = -F^{(n)}(s) \leftrightarrow t^n f(t)[/tex]

and it follows that

[tex]F^{(n+1)}(s) = \displaystyle \frac{d}{ds} \left[-\int_0^\infty t^n f(t) e^{-st} \, dt \right][/tex]

[tex]F^{(n+1)}(s) = \displaystyle -\int_0^\infty \frac{\partial}{\partial s}\left[ t^n f(t) e^{-st} \right] \, dt[/tex]

[tex]F^{(n+1)}(s) = \displaystyle \frac{d}{ds} \left[-\int_0^\infty t^n f(t) e^{-st} \, dt \right][/tex]

[tex]F^{(n+1)}(s) = \displaystyle \int_0^\infty t^{n+1} f(t) e^{-st} \, dt[/tex]

[tex]\implies F^{(n+1)}(s) = (-1)^{n+1} F^{(n+1)}(s) \leftrightarrow t^{n+1}f(t)[/tex]

• Otherwise, if k = n + 1 is odd, then n is even, so

[tex](-1)^n F^{(n)}(s) = F^{(n)}(s) \leftrightarrow t^n f(t)[/tex]

The rest of the proof is the same as the previous case.

So we've proved the claim by induction:

• [tex]t f(t) \leftrightarrow -F(s)[/tex], and

• [tex]\bigg(t^n f(t) \leftrightarrow (-1)^n F^{(n)}(s)\bigg) \implies \bigg(t^{n+1} f(t) \leftrightarrow (-1)^{n+1} F^{(n+1)}(s)\bigg)[/tex]